2016
DOI: 10.1016/j.jare.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Metallurgical and mechanical properties of laser welded high strength low alloy steel

Abstract: The study aimed at investigating the microstructure and mechanical properties of Neodymium-Doped Yttrium Aluminum Garnet (Nd:YAG) laser welded high strength low alloy (HSLA) SA516 grade 70 boiler steel. The weld joint for a 4 mm thick plate was successfully produced using minimum laser power of 2 kW by employing a single pass without any weld preheat treatment. The micrographs revealed the presence of martensite phase in the weld fusion zone which could be due to faster cooling rate of the laser weldment. A go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 24 publications
(21 reference statements)
5
20
0
1
Order By: Relevance
“…Experimentally obtained results correspond to the relevant literature sources, such as Pamnani et al [28], Nathan et al [29], Haribalaji, Boopathi and Balamurugan [30], Oyyuaravelu [31], and Values of the cooling time t 8/5 were obtained within range 28.5 to 32 s. Different theoretical formulas predict that values could range from 24 s (Ito-Bessyo formula) to 65 s (formula of limited thickness) [25], so the experimentally obtained values are in compliance with theoretically predicted ones.…”
Section: Discussionsupporting
confidence: 83%
“…Experimentally obtained results correspond to the relevant literature sources, such as Pamnani et al [28], Nathan et al [29], Haribalaji, Boopathi and Balamurugan [30], Oyyuaravelu [31], and Values of the cooling time t 8/5 were obtained within range 28.5 to 32 s. Different theoretical formulas predict that values could range from 24 s (Ito-Bessyo formula) to 65 s (formula of limited thickness) [25], so the experimentally obtained values are in compliance with theoretically predicted ones.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, various morphologies (i.e., columnar and equiaxed) in FZ could be a reason for the various hardness. However, some researchers have focused to determine an empirical formula for FZ hardness using CE values; in the present study, the measured hardness of FZ is higher than the calculated values using the mentioned formulas [31,36]. The calculated hardness values using the formulas given in the literature are 434 HV and 365 HV.…”
Section: Microstructure and Microhardness Evolutionmentioning
confidence: 61%
“…where f(C) is the accommodation factor and is calculated as; In the welding process, final microstructures are affected by peak temperature and the cooling rate of the relevant zones, and carbon equivalent (CE) value resulted from the chemistry of the steels [29][30][31][32]. Although there are numerous formulae for calculating CE, Yurioka's formula was used in this study because of its suitability for C-Mn steels [33].…”
Section: Microstructure and Microhardness Evolutionmentioning
confidence: 99%
“…It was also found that suitable SAW factors improved both tensile strength and hardness properties, which affect the pearlite density in the ferrite phase shown in Figure 6. Oyyaravelu et al [19] reported that the highest hardness and tensile strength clearly prompted the formation of martensite and pearlite phases in the weld metal and heat-affected zone. Related observations have been made by Lah et al [20], where the highest mechanical properties of pressure vessel steel weld were a result of pearlite density and fine pearlite phase.…”
Section: Microstructure Observationsmentioning
confidence: 99%